Primary heart failure with preserved ejection fraction: The intertwined pathophysiology and treatment of some of the most relevant phenotypes - Ryohei Ono; Luiz Menezes Falcão (Revista Portuguesa de Cardiologia)
Heart failure with preserved ejection fraction (HFpEF) is characterized by diverse underlying pathophysiological mechanisms and can be divided into two subgroups based on the identification of the specific cause: primary and secondary HFpEF. Primary HFpEF is caused by primary impairments in myocardial relaxation or compliance with the contribution of several risk factors. Therefore, we have reviewed current literature on pathophysiology and treatment in patients with primary HFpEF. Patients with primary HFpEF represent specific “phenotypes” and are usually elderly, more commonly women, and often with a history of arterial hypertension, obesity, iron deficiency (ID), coronary artery disease (CAD), sleep apnea, diabetes, chronic kidney disease (CKD), and chronotropic incompetence. Some of the main pathophysiological mechanisms for each phenotype of primary HFpEF are as follows: arterial hypertension, which promotes left ventricular hypertrophy and fibrosis; obesity, which contributes through systemic inflammation and metabolic dysregulation; aging, which leads to ventricular-vascular stiffening; gender differences, with women experiencing changes due to smaller heart size and hormonal shifts; ID, which affects mitochondrial function; CAD, which impairs myocardial blood flow; diabetes, which is associated with hyperglycemia, lipotoxicity, insulin resistance, and microvascular rarefaction; CKD, which leads to hypertension, metabolic disturbance, systemic inflammation, and endothelial dysfunction; sleep apnea, which induces cardiac changes through pressure swings and hypoxia; and chronotropic incompetence, which is due to reduced cardiac β-receptor responsiveness. In conclusion, each factor intricately contributes to the complex pathophysiology of HFpEF. Understanding these interrelated mechanisms is critical for tailoring management strategies to improve outcomes in HFpEF patients. Resumo: A insuficiência cardíaca com fração de ejeção preservada (ICpFE) é consequência de diversos mecanismos fisiopatológicos e pode ser dividida em dois grupos tendo por base a identificação da causa específica: primária ou secundária. A ICpFE primária é causada pela perturbação primária do relaxamento ou da distensibilidade miocárdica com a contribuição de vários fatores de risco. Neste artigo, é feita uma revisão da fisiopatologia e do tratamento de algumas das formas de apresentação mais relevantes de ICpFE primária. Os doentes com ICpFE primária representam «fenotipos» específicos e são habitualmente idosos, do sexo feminino e mais frequentemente têm uma história de hipertensão arterial, obesidade, deficiência de ferro, doença coronária, apneia do sono, diabetes mellitus, doença renal crónica e de incompetência cronotrópica. Alguns dos principais mecanismos fisiopatológicos de cada fenótipo da ICpFE primária são os seguintes: hipertensão arterial, que promove hipertrofia ventricular esquerda e fibrose; obesidade que ocasiona inflamação sistémica e desregulação metabólica; envelhecimento que contribui para a rigidez ventriculo-vascular; diferenças entre sexos com o sexo feminino expressando-se com coração de menores dimensões e oscilações hormonais; deficiência de ferro contribuindo para a disfunção mitrocondial; doença coronária ocasionando redução do fluxo sanguíneo miocárdico; diabetes mellitus, que está associada com hiperglicémia, lipotoxicidade, resistência à insulina e rarefação microvascular; doença renal crónica, que ocasiona hipertensão arterial, perturbação metabólica, inflamação sistémica e disfunção endotelial;apneia do sono, que induz variações tensionais e hipóxia; e incompetência cronotrópica que se deve a redução da resposta dos recetores beta adrenérgicos. Em conclusão, cada fator interage com outros fatores contribuindo para o complexo fisiopatológico da ICpFE. A compreensão destes mecanismos interrelacionados é crítica para estabelecer estratégias terapêuticas adequadas para melhorar o prognóstico da ICpFE.